Research Progress on Relation Between YTHDF1 and Tumors - XIAO Shiwei; WANG Haifeng; WANG Jiansong; DING Mingxia (Zhongliu Fangzhi Yanjiu, 2020)
N6-methyladenosine (m6A) modification is the most common, abundant and conservative posttranscriptional modification. More and more evidence suggest that via various mechanisms, it has a certain impact on tumors, such as liver cancer, gastric cancer, lung cancer, bladder cancer and melanoma. It has been found that YTHDF1, as a kind of m6A-modification binding protein, plays an important role in tumor transcription, translation, protein synthesis, immune escape, EMT, chemotherapy resistance and so on. It is expected to find new methods for the diagnosis and treatment of cancer by revealing the mechanism of YTHDF1. This article reviews the research progress in this field.